Cape Verde : Poverty Reduction Strategy Paper; First Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
The Joint Staff Advisory Note (JSAN) reviews the First Annual Progress Report (APR) of Cape Verde on the Poverty Reduction Strategy Paper (PRSP) under the Policy Support Instrument (PSI). The JSAN recommends that the timeliness and reliability of data for the monitoring and evaluation of the PRSP be improved. The APR focuses on recent steps and reform priorities to strengthen public financial management and budget processes. The report gives particular emphasis to measures undertaken and plans to strengthen audit processes, budget prioritization, procurement practices, and revenue collection.